Lower conditioning leisure-time physical activity in young adults born preterm at very low birth weight. - Nina Kaseva (Public Library of Science (PLoS), 2012)
Background Adults born preterm at very low birth weight (VLBW, <1500 g) have elevated levels of risk factors for cardiovascular diseases and type 2 diabetes. Preliminary observations suggest that this could partly be explained by lower rates of physical activity. The aim of this study was to assess physical activity in healthy young adults born preterm at very low birth weight compared with term-born controls. Methodology/principal findings We studied 94 unimpaired young adults, aged 21-29 years, born at VLBW and 101 age-, sex-, and birth hospital-matched term-born controls from one regional center in Southern Finland. The participants completed a validated 30-item 12-month physical activity questionnaire and the NEO-Personality Inventory based on the Big Five taxonomy, the most commonly used classification of personality traits. Yearly frequency, total time, total volume and energy expenditure of conditioning and non-conditioning leisure-time physical activity (LTPA) and commuting physical activity were compared between VLBW and term-born subjects. A subset of participants underwent dual-energy x-ray absorptiometry for body composition measurement. Data were analyzed by multiple linear regression. Compared with controls, VLBW participants had lower frequency [-38.5% (95% CI; -58.9, -7.7)], total time [-47.4% (95% CI; -71.2, -4.1)], total volume [-44.3% (95% CI; -65.8, -9.2)] and energy expenditure [-55.9% (95% CI; -78.6, -9.4)] of conditioning LTPA when adjusted for age, sex, body mass index, smoking, parental education and personality traits. Adjusting for lean body mass instead of body mass index attenuated the difference. There were no differences in non-conditioning LTPA or commuting physical activity. Conclusions/significance Compared with term-born controls, unimpaired VLBW adults undertake less frequent LTPA with lower total time and volume of exercise resulting in lower energy expenditure. Differences in personality that exist between the VLBW and term-born groups do not seem to explain this association.